Evaluación del ciclo de vida de las películas de la mezcla Tio2 /Cuo para la inactivación fotocatalítica de la E.coli en presencia de luz visible (2018)
In the present work of degree was carried out the elaboration of the mixture of TiO2 / CuO by means of two methods of impregnation, in which the concentration of the precursor solution CuSO4 was varied, in the same way the method of deposition by spin coating and the necessary amount of suspension to deposit. The calcination temperature of 600ºC established in the group of Photoactive Materials was maintained. The characterization of the mixtures was carried out by scanning electron microscopy (SEM) and x-ray diffraction (XRD). To realize the life cycle of the films, they were subjected to methylene blue removal tests, which proved their functionality. Once checked, the photodegradative process of the films of the TiO2 / CuO mixture begins in the presence of the E. coli bacterium in order to inactivate the microorganism in the presence of visible light in an estimated time of 9 hours. Once the time was completed, the surface plate count method was used to quantify the CFU / mL obtaining a reduction of nine logarithmic units compared to the initial CFU / mL. Data of 99.99% elimination of the bacteria was obtained in the first three uses of the TiO2 / CuO mixture film. In its fourth use, an efficiency drop of 47.85% was obtained, verifying that the method is repeatable .